Stressors and well-being in low socio-economic status Malaysian adolescents: the role of resilience resources - Noor, Noraini M.; Alwi, Azlin (Blackwell Publishing Asia Pty Ltd, 2013)
The present study examined the relationship between stressors, resilience resources, and well-being in adolescents with low socio-economic status in Malaysia. The specific aims were: (i) to differentiate between resilient and non-resilient adolescents in terms of their resilience resources; and (ii) to examine the role of resilience resources on the relationship between stressors and well-being. In a sample of 197 adolescents aged 12–16 years (mean = 13.77, sd = 1.49), results of the k-mean clustering technique identified 37.5% of the adolescents as resilient (high stressor, high well-being), 31.0% as maladjusted (high stressor, low well-being), and the rest, adapted (low stressor, high well-being). Resilient adolescents were found to have significantly higher scores on all the identified resilience resources (personality, mother–child communication, social support, school coherence, and teacher support) compared to the non-resilient maladjusted group. Results of structural equation modelling also showed that these resilience resources acted both as mediator and moderator in the relationship between stressors and well-being. These findings are discussed with respect to the current literature on resilience and well-being.